Biochemical evidence on the potential role of methyl mercury in hepatic glucose metabolism through inflammatory signaling and free radical pathways. Issue 9 (12th May 2019) - Maqbool, Faheem; Bahadar, Haji; Hassani, Shokoufeh; Niaz, Kamal; Baeeri, Maryam; Rahimifard, Mahban; Ghasemi‐Niri, Seyedeh Farnaz; Abdollahi, Mohammad
Abstract: Methylmercury (MeHg) is an extremely important environmental toxicant posing serious health risks to human health and a big source of environmental pollutant. Numerous evidence available showing a link between nervous system toxicity and MeHg exposure. Other forms of mercury are reason of metabolic toxic effects and alteration of DNA in the human body. The sources of exposure could be occupational or other environmental settings. In the present study MeHg was orally gavaged to mice, at doses of 2.5, 5, and 10 mg/kg for 4 weeks. Fasting hyperglycemia, activity of hepatic phoshphoenolpyruvate carboxykinase and glucose 6‐phoshphate were reported high as compared to control group. Inflammatory markers like, tumor necrosis factor α, the actual end product of inflammatory mediators' cascade pathway was also raised in comparison to control group. Hyperinsulinemia observed in serum showed clear understanding of mercury induced insulin resistance. Moreover, tissue damage due to increased oxidative stress markers like, hepatic lipid peroxidation, 8‐deoxygunosine, reactive oxygen species, and carbonyl groups was significantly higher as compared to control group. MeHg caused a significant reduction in antioxidant markers like ferric reducing antioxidant power and total thiol molecules. The present study highlighted that activity of key enzymes involved in glucose metabolism is changed, owing to MeHg induced toxicity in the liver. Induction of similar toxic effects assumed to be stimulated by the production of high quantity free radicals. Abstract : Potential toxicity of methylmercury in the liver.